Reversal of cardiac damage in patients with symptomatic severe aortic stenosis following transcatheter aortic valve implantation: An echocardiographic study - Chung, B.K.; Chan, En Ze; Thien, L.K.; Chan, D. S. T.; Khor, H. K.; Shu, F.E.P.; Ling, Hwei Sung; Chow, H.B.; Jong, Sin Yen; Soon, S. Y.; Koh, K.T.; Cham, Y.L.; et al. (Elsevier B.V., 2022)
Background: Severe aortic stenosis (AS) results in cardiac damages, such as left ventricular hypertrophy, left atrial enlargement, pulmonary pressure elevation and in advanced stage, right ventricular damage. Généreux and colleagues proposed a staging classification based on these extra-valvular damages in 2017, with increasing stage representing more cardiac damage. While regression of these cardiac damages is expected following aortic valve replacement, the reversal of cardiac damage based on this staging system has not been described. Purpose: This study aimed to describe and stage the changes in cardiac structure and function at 6 months and 1 year after transcatheter aortic valve implantation (TAVI) in patients with symptomatic severe AS. Methods: This was a retrospective, single center, longitudinal observational study. Echocardiographic data of patients who underwent TAVI were retrieved and analysed. Results: From May 2018 to Feb 2021, 31 patients underwent TAVI. 5 patients were excluded due to death <6 months post-procedure (n=2) and incomplete echocardiographic data (n=3). The mean age of the remaining 26 patients was 70.9±9.4 years, 57.7% were male, and 34.6% bicuspid aortic valve. After TAVI, transvalvular aortic mean pressure gradient reduced from 45.2±14.5 mmHg to 8.0±5.4 mmHg (p<0.001), and aortic valve area increased from 0.57±0.21 cm2 to 1.75±0.68 cm2 (p<0.001). At baseline, 6-month and 1-year, the left ventricular mass index (LVMi) were 183.4±60.7g/m2, 150.8±55.3 g/m2 and 126.8±42.1 g/m2 (p<0.001) respectively; left-atrial volume index (LAVI) were 60.4±22.8 ml/m2 , 51.7±23.8ml/m2, and 48.1±23.6ml/m2 (p=0.009) respectively; left ventricular ejection fraction (LVEF) were 52.3±25.4%, 64.2±29.3%, and 62.4±12.1% (p=0.005) respectively. Based on the proposed cardiac damage staging for AS, at baseline 38% of patients were stage 1, 65.4% stage 2, 7.7% stage 3 and 23.1% stage 4. At 1 year, 8.3% were stage 0, 29.2% stage 1, 58.3% stage 2, and 4.2% stage 4. 12 patients (46%) showed improvement in cardiac damage staging, and the other 14 (54%) remained in the same stage. Conclusion: In patients with symptomatic severe AS, there were overall significant regression in LVMi and LAVI, and improvement in LVEF at 1 year after TAVI. However, improvement in cardiac damage staging was observed in only 46% of patients.